MENENTUKAN MASA DEPAN KEPARIWISATAAN DAERAH ISTIMEWA YOGYAKARTA - , DWI ERNAWATI, Prof. Dr. Warsito Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the process of policy formulation DIY provinsial regulations about tourism development master plan year 2010-2025 an indispensableas DIY has a variety of tourism potential, and material, especialy about marketing. With superior competitors from other regions, then it is a challenge for DIY to bring tourists, both national and international. A careful planning is required, until the material is representatif to market a tourism products.DIY were selected for study because it is an area with tremendous tourism potential, and is the first provinsi who follow the national tourism development master plan in 2010-2025. The research informant was the head of DIY tourism department with some staff, chairman of the parliament DIY, and chairman of the special commitee draft Ripparda DIY. This is a descriptive study design by using the techniques of data collection by interviewing informants directly, observation, and analyzing documents related to research. The analysis uses a qualitative descriptive approachby exploring all things related, trough the stages of description, reduction, selection, as well as decision making and verification. To ensure the validity of data obtained, the researchers conducted data triangulation. The goal is to know the process of formulating Ripparda DIY year 2010-2025, and determine the suitability of the material on marketing between Ripparda with Ripparnas. The results obtained from this study is that all stakeholders feel the need for regulation of tourism in DIY because it will be a guide in carrying out its activities in the field. In addition, the Ripparda is a mandate from tourism legislation that calls for the tourism master plan at the national and regional. Formulation process has been through the stages that should be there in the formulation of a public policy, ranging from problem definition, agenda, selection of alternatives, and the establishment of policies. All stages are involving all stakeholders, which had a material interest in the policy each. There was certainly conflicts, but the desire to bring together a representative rule makes the conflict was prolonged. Marketing material about the ripparda is the results of stakeholders sharing opinions and remain guided by the material ripparnas, so ripparda accordance with ripparnas, although seem like just âcopy pasteâ. Therefore, the researchers suggests is policy makers need to consults directly with the community by visiting them, as well as legislative and tourism department need to be more aware about tourism that new regulations be made more innovative and creative.